Соцреалізм пастка для письменника або Євангеліє від Бейло Юнгера - Юнгер, Михайло Бейлович (SlavVaria, 2023)
Social realism is a trap for the writer or the Gospel by Béla Junger. The article addresses with the issue that was especially relevant in the second half of the twentieth century in the Soviet Union. Namely, the influence of the only officially recognized creative method – socialist realism on creativity, and thus on human destiny, particularly, on the writer. Six dramatic works by B. Junger are analyzed. It’s determined, that the author’s consideration of the requirements of socialist realism has greatly influenced the stage fate of the plays. It is established that only liberation from the tenets of socialist realism made it possible to create a work that contributed to further developing the creative potential of the writer and the individual.